ANALYSIS OF THE ACHIEVEMENTS OF THE IMPLEMENTATION OF THE ADOLESCENT REPRODUCTIVE HEALTH INFORMATION AND COUNSELING CENTER PROGRAM (PIK-KRR ) IN THE CITY OF BUKITTINGGI - syahril, Oktavianis; -, Nurhayati; -, Athosra; Husna, Riyana; Sari, Dhita Ananda (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
PIK-KRR is one of the adolescent health programs as a preventive effort towards adolescent reproductive health. Data from KESRA, BKKBN and the Health Office of Bukittinggi City, the implementation of the PIK-KRR program in Bukittinggi City has been running but the implementation has not been optimal because the existence of PIK KRR in Bukittinggi City is not in every school, there are only 8 PIK KRR spread across SMA / SMK / MA in Bukittinggi City. This study aims to analyze the achievement of the implementation of the PIK-KRR program in Bukittinggi City. This type of research is a qualitative description with the selection of informants using purposive sampling, namely all elements related to the implementation of PIK-KRR: Health office, DP3AP2KB, Puskesmas, high school, and aggregate adolescents in the school and community environment. Data collection in this study used in-depth interviews and observation. Data analysis used collaizi technique. The results showed that the achievement of the implementation of the PIK-KRR program in Bukittinggi City was still low, especially the low interest of adolescents to participate and take advantage of the PIK-KRR program, this was influenced by factors such as the lack of commitment of policy-making parties and cross-sector program implementers, lack of funds, infrastructure and incompetent human resources. Therefore, it is expected that all relevant parties can take steps and strategies to strengthen the implementation of the PIK-KRR program in Bukittinggi City.